Effect of Neuromuscular Electrical Stimulation on Swallowing Process in Stroke Patient with Neurogenic Dysphagia - Ruth Ariyani; Widjajalaksmi; Luh K Wahyuni; Susyana Tamin; Saptawati Bardosono (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objective: The aim of this study to determine the therapeutic effect of Neuromuscular Electrical Stimulation (NMES) on pharyngeal phase of swallowing for stroke patients with neurogenic dysphagia,and to see the effect of NMES in reducing the incidence of standing secretion, residue, penetration and aspiration.Methods: It is a quasi-experimental study design. 10 stroke patients with neurogenic dysphagia in Cipto Mangunkusumo hospital, Jakarta, 40-80 years old with hemodynamically stable, cooperative and will be get NMES therapy for 4 weeks. Pre and Post treatment assessment caompared using a modified MASA test (The Mann Assessment of Swallowing Ability) and FEES examination (Flexible Endoscophic Evaluation of Swallowing). Analysis of change scores using Wilcoxon test.Results:The obtain average age of patients 59.80+9.705 years. Significant difference seen in the pharyngeal phase of swallowing increased score of gag reflex, velum elevation, cough reflex, voluntary cough, voice quality, pharynx response, pharyngeal constrictor contraction and vocal cord adduction (p<0.005).Also seen significant reduction in the incidence of standing secretion, residue and penetration (p<0.005), but not significantly in the incidence of aspiration (p=0083).Conclusions: NMES increased the pharyngeal phase of swallowing, reduced the incidence of standing secretion, residue and penetration of stroke patients with neurogenic dysphagia, but have not able to reduced aspiration.Keywords :Neuromuscular Electrical Stimulation (NEMS), neurogenic dysphagia, MASA test (The Mann Assessment of Swallow ing Ability), FEES examination (Flexible Endoscophic Evaluation of Swallowing), swallowing process.